New Testament questions of today - Kasemann, Ernst (London SCM, 1969)
Includes bibliographical references, Scripture index and other index.
Translated by W.J. Montegue from selections from the German Exegetische Versuche und Besinnungen, Zwieter Band. Chapter 12 " Paul and early Catholicism" translated by Wilfred F Bunge for ( and reprinted from) "Distinctive Protestant and Catholic themes reconsidered" (Journal for theology and the church, vol 3).
Keywords: Bible N.T. -- themes